2021
DOI: 10.1126/scisignal.abf6685
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent changes in binding partners and post-translational modifications regulate the abundance and activity of HIF-1α/2α

Abstract: Cellular adaptation to low-oxygen environments is mediated in part by the hypoxia-inducible factors (HIFs). Like other transcription factors, the stability and transcriptional activity of HIFs—and consequently, the hypoxic response—are regulated by post-translational modifications (PTMs) and changes in protein-protein interactions. Our current understanding of PTM-mediated regulation of HIFs is primarily based on in vitro protein fragment–based studies typically validated in fragment-expressing cells treated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…The activity of HIF, although primarily controlled by the activity and availability of the HIF-α subunits by PHDs and VHL, can be modulated and tuned by other modifying enzymes and interacting proteins [3][4][5]84]. Unbiased MS experiments have revealed that the PTM landscape and interaction partners if HIF transcription factors are in fact extremely complex [82,85]. The phosphosite plus repository of post-translational modifications of individual proteins either identified from MS or throughput approaches, reveals that HIF-1α, HIF-2α, HIF-3α and HIF-1β have 73, 39, 20 and 29 unique PTMs, respectively [86,87].…”
Section: Advances In Understanding Hif Signalling By Mass Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations
“…The activity of HIF, although primarily controlled by the activity and availability of the HIF-α subunits by PHDs and VHL, can be modulated and tuned by other modifying enzymes and interacting proteins [3][4][5]84]. Unbiased MS experiments have revealed that the PTM landscape and interaction partners if HIF transcription factors are in fact extremely complex [82,85]. The phosphosite plus repository of post-translational modifications of individual proteins either identified from MS or throughput approaches, reveals that HIF-1α, HIF-2α, HIF-3α and HIF-1β have 73, 39, 20 and 29 unique PTMs, respectively [86,87].…”
Section: Advances In Understanding Hif Signalling By Mass Spectrometrymentioning
confidence: 99%
“…However, this is likely to be an underestimation of the real level of PTMs present. Recent detailed analysis specifically analysing phosphorylation of HIF-1α and HIF-2α identified 41 and 39 different phosphosites on HIF-1α and HIF-2α respectively, including evidence of non-canonical phosphorylation of cystine residues [ 85 ]. Critically this study examined changes to the phosphorylation landscape on HIF-1α and HIF-2α in response to both normal oxygen and hypoxic conditions in cervical carcinoma cells [ 85 ].…”
Section: Advances In Understanding Hif Signalling By Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Both HIF-1 and HIF-2 heterodimers recognize and bind to the 5′-ACGTG-3′ enhancer sequence, resulting in the transcriptional regulation of more than a thousand genes [ 10 , 11 ]. The abundance and activity of both HIF-1α and HIF-2α can also be enhanced due to post-translational modifications [ 12 ]. HIF-regulated genes have been associated with angiogenesis, apoptosis, cell proliferation, cell survival, metabolism, invasion, metastasis, altered pH, and chemoresistance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%